MODELING OF COMMUNITY RELOCATION AFFECTED BY THE SEMERU VOLCANIC ERUPTION IN LUMAJANG REGENCY - Haq, Thoriqul; Pandin, Moses Glorino Rumambo (Universitas Airlangga, 2024)
The relocation program established to prepare new areas for refugees to prevent them from returning to vulnerable areas is the new area of APG Semeru. This area is referred to as temporary housing (Huntara) for victims of the Semeru eruption. The implementation process is considered highly mature as it involves many parties, including Non-Governmental Organizations such as Banser Bagana, Pramuka Peduli, and even the Indonesian Architects Association. Such synergy is crucial as it is assumed to support innovations in the new area to make it more suitable. The modeling referred to is a series of important stages carried out in disaster relocation policy management. As mentioned earlier, there are several important aspects to be examined in the effectiveness of relocation programs, namely target perceptions, collaboration, and forms of policies implemented. The research uses qualitative research model. The results of this study are: First, dynamics occur from the communication, planning, implementation to development stages. In the communication stage, differences in rationalism and empiricism regarding disasters occur. In planning, actual participation is involved, while in the implementation to development stages, it is always related to unmet needs. Second, to succeed in relocation, there are several forms of policies that must be formulated, such as emergency response policies, mitigation team formation, relocation policies, cooperation and collaboration, post-relocation, and budget policies. The initial policies implemented are related to disaster conditions, while others follow the analysis results of emergency conditions, recovery, or have entered the development stage. All policies are tailored to real-time needs analysis. Additionally, they are all formulated with policy formation, collaboration, and budget stages. Third, the policy implementation model for relocation appears to develop previous theoretical ideas or findings. Several stages such as Jitu Pasna, land clearance, infrastructure and service access, economic and social development need to be implemented with additional policy principles or elements. These include collaborative policies, budget management, and politics.